Realitas Silent Treatment dalam Hubungan Interpersonal Berpacaran pada Perempuan Dewasa Muda: (Studi Fenomenologi pada Mahasiswi Universitas Langlangbuana Angkatan 2021) - Sukma, Anggita Nurul; Salim, Rodhiyat Fajar; Rachaju, Rannie Dyah Khatamisari (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to describe the reality experienced by young adult women who have faced silent treatment in romantic relationships, with a focus on female students at Langlangbuana University Bandung. Silent treatment is understood as a deliberate withdrawal from communication, often used in response to conflict, and can lead to emotional pressure, confusion, and intrapersonal communication issues. Using a qualitative approach and Alfred Schutz’s phenomenological method, this study explores the subjective meanings behind these experiences. In-depth interviews were conducted with three participants who had been in relationships lasting over a year, which ended due to prolonged silence. The findings reveal that silent treatment results in anxiety, guilt, and diminished self-confidence. Moreover, the intrapersonal responses to such behavior tend to deepen inner conflict and hinder emotional recovery. This phenomenon is particularly significant for young adult women as they navigate identity formation and emotional stability. The study highlights the urgency of emotional communication literacy and safe relational environments to support healthier dynamics. These insights contribute to the development of intrapersonal communication studies and the understanding of strained romantic relationships.